2022
DOI: 10.1111/mec.16554
|View full text |Cite
|
Sign up to set email alerts
|

Two hundred and five newly assembled mitogenomes provide mixed evidence for rivers as drivers of speciation for Amazonian primates

Abstract: Mitochondrial DNA remains a cornerstone for molecular ecology, especially for study species from which high-quality tissue samples cannot be easily obtained. Methods using mitochondrial markers are usually reliant on reference databases, but these are often incomplete. Furthermore, available mitochondrial genomes often lack crucial metadata, such as sampling location, limiting their utility for many analyses. Here, we assembled 205 new mitochondrial genomes for platyrrhine primates, most from the Amazon and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 163 publications
1
9
0
Order By: Relevance
“…Mitochondrial (mt) genes have a long history of use for phylogenetic reconstruction in animals 1 , and the relative ease with which complete mt genomes can now be obtained has fueled an increase in their use to resolve phylogenetic relationships within many groups 2 4 . Animal mt genomes typically include a highly conserved set of protein-coding genes with few non-coding intergenic regions; are inherited uniparentally without undergoing recombination; and in many cases have rates of substitution that may be an order of magnitude higher than those of the nuclear genome 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial (mt) genes have a long history of use for phylogenetic reconstruction in animals 1 , and the relative ease with which complete mt genomes can now be obtained has fueled an increase in their use to resolve phylogenetic relationships within many groups 2 4 . Animal mt genomes typically include a highly conserved set of protein-coding genes with few non-coding intergenic regions; are inherited uniparentally without undergoing recombination; and in many cases have rates of substitution that may be an order of magnitude higher than those of the nuclear genome 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This large dataset of mitochondrial genomes further demonstrates the utility of off-target reads generated from target-capture data for mitochondrial genome assembly and adds to the growing knowledge of anthozoan evolution. d r a f t Introduction Mitochondrial (mt) genes have a long history of use for phylogenetic reconstruction in animals [1], and the relative ease with which complete mt genomes can now be obtained has fueled an increase in their use to resolve phylogenetic relationships within many groups [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial (mt) genes have a long history of use for phylogenetic reconstruction in animals [1], and the relative ease with which complete mt genomes can now be obtained has fueled an increase in their use to resolve phylogenetic relationships within many groups [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fluck et al (2020) found that temperature and precipitation were more important than rivers in terms of explaining species composition across Amazonia. This conclusion is surprising because Amazonian rivers are known to delineate the distributions of hundreds of avian taxa and are widely recognised as dispersal barriers for birds and other terrestrial taxa (Byrne et al, 2021;Capparella, 1988Capparella, , 1991Cracraft, 1985;Haffer, 1985;Janiak et al, 2022;Mourthé et al, 2022;Ribas et al, 2012;Sick, 1967;Silva et al, 2019). Whether the results obtained by Fluck et al (2020) would have changed if these authors used avian subspecies is worth exploring.…”
Section: How Does Taxonomic Scale Influence Downstream Analyses?mentioning
confidence: 99%